Lego Ninjago, masters of Spinjitzu. / bk. 07, Stone cold - Farshtey, Greg (Lego Ninjago graphic novels, 2013)
"Jay, Cole, Zane, Kai, and Sensei Wu are strangers in an even stranger land-- Garmadon City! But the name is not what's strange! The fact that everything is made of stone-- the streets, the buildings, the trees, even the people!-- that's the really strange part. But how do you save people who have been turned into stone who don't want to be saved, and will do anything to stop you?"--P. [4] of cover.